IMPLEMENTASI MUSYAWARAH SEBAGAI TEKNIK PROBLEM-FREE TALK UNTUK PEMECAHAN MASALAH KONSELING ISLAMI - Azhara, Siti; Nurjannah, Nurjannah (At-Taujih : Bimbingan dan Konseling Islam, 2024)
This study aims to explore the potential of applying the Problem-Free Talk Technique in the context of deliberation to solve problems in Islamic counseling. Deliberation is considered a participatory dialog method that involves participants in seeking solutions together. The Problem-Free Talk technique, which emphasizes positive potential and solutions, so that it can be an effective approach to reaching an agreement in the context of Islamic counseling. The research method used is Library research by collecting reading materials from various sources and involving literature analysis related to deliberation, Islamic counseling, and the Problem-Free Talk Technique. The results of the analysis support the idea that the integration of the Problem-Free Talk Technique in deliberation can open a harmonious discussion space and allow participants to focus on solutions rather than problems, by supporting effective and positive communication is expected to make a positive contribution to problem solving in Islamic counseling. The Problem-Free Talk Technique can advance the Solution Focused Brief Therapy (SFBT) centered counseling approach as well as provide practical guidance for Islamic counselors in dealing with complex problems.